Contemporary Role of Embolization of Solid Organ and Pelvic Injuries in Polytrauma Patients - Ptohis, Nikolaos D.; Charalampopoulos, Georgios; Abou Ali, Adham N.; Avgerinos, Efthymios D.; Mousogianni, Iliana; Filippiadis, Dimitrios; Karydas, George; Gravanis, Miltiadis; Pagoni, Stamatina (Frontiers in Surgery, 2017)
Abdominopelvic trauma remains a leading cause of morbidity and mortality in the 15- to 44-year-old age group in the Western World. It can be life-threatening as abdominopelvic organs, specifically those in the retroperitoneal space, can bleed profusely. Abdominopelvic trauma is divided into blunt and penetrating types. While surgery is notably considered as a definitive solution for bleeding control, it is not always the optimum treatment for the stabilization of a polytrauma patient. Over the past decades, there has been a shift towards more sophisticated strategies, such as non-operative management of abdominopelvic vascular trauma, for haemodynamically stable patients. Angiographic embolization for bleeding control following blunt and/or penetrating intra- and retroperitoneal injuries has proven to be safe and effective. Embolization can achieve haemostasis and salvage organs without the morbidity of surgery, and the development and refinement of embolization techniques has widened the indications for non-operative treatment in solid organ injury. Moreover, advances in computed tomography provided more efficient scanning times with improved image quality. Whilst surgery is still usually recommended for patients with penetrating injuries, non-operative management can be effectively used as well as an alternative treatment. We review indications, technical considerations, efficacy and complication rates of angiographic embolization in abdominopelvic trauma.